GUDUCHI AS A RASAYANA IN INFECTIOUS DISEASES: A REVIEW - R, *Lekshmi; kumar, Krishna; Mishra, Ratnaprava; Chacko, James (International Journal of Ayurveda and Pharma Research, 2016)
Disease is the outcome of combination of vitiated Dosha and Dooshya which happens when Vyadhikshamatwa (immunity) is decreased. Because of the lifestyle and changing environment, the immunity of people is decreasing day by day making them prone for getting afflicted with infectious diseases. The present day infectious diseases like Dengue, H1N1, AIDS, TB etc. are only due to lowered immunity. Rasayana is believed to promote the process of Dhatuposhana and enrich Ojas leading to Vyadhikshamatva. The concept of Rasayana therapy is a comprehensive and specialized regimen capable of producing healthful longevity and improved mental faculties by acting at the level of Rasa, Agni and the Srotas, thus enabling the organism to procure the best qualities of different Dhatus. Guduchi is considered one of the best Rasayanas and is unusual in its potent versatility. The significant actions of Guduchi include promoting Bala (cellular and humoral immunity), Agnideepana, cures fever, eliminates Ama (metabolic wastes and toxins), skin diseases, Upper respiratory tract infections, gout etc. It can be used as Swarasa, Kashaya, Satwa for internal use or as paste for external application in skin diseases to get the desirable effect. Guduchi is known to be a rich source of trace elements which act as antioxidants. It is apt to get the name Amrita because it itself can regenerate and can bring back the diseased cells to normalcy. So this article aims at making a public awareness of the use of Guduchi as a Rasayana in maintaining health and in the treatment of infectious diseases.